Con(des)figurações de família no teatro de Nelson Rodrigues: um enfoque histórico (1941/1965) - Valli, Marcia (2013)
The objective of this dissertation is to find out in the theatrical pieces of Nelson Rodrigues settings family by him used during the decades 1941/1965, that derived of the patriarchal model, burgues and originated of the popular classes, with the intention of catching the way of life and customs family altered by the economic and social transformations of the period, registered in his literature